Organic-inorganic hybrid solid electrolytes for solid-state lithium cells operating at room temperature. (10th November 2016) - Jung, Yun-Chae; Park, Myung-Soo; Doh, Chil-Hoon; Kim, Dong-Won
Highlights: Hybrid solid electrolytes were prepared and their electrochemical properties were investigated. They showed high ionic conductivity, good electrochemical stability and favorable interfacial characteristics with an addition of succinonitrile. The solid-state Li/LiFePO4 cell with hybrid solid electrolyte exhibited good cycling performance at room temperature. Abstract: Organic-inorganic hybrid solid electrolytes composed of Li + -conducting lithium aluminum germanium phosphate (LAGP), poly(ethylene oxide) (PEO), lithium perchlorate and succinonitrile (SN) were prepared in the form of flexible thin film, and their electrochemical properties were investigated. The hybrid solid electrolytes showed high ionic conductivities ranging from 3.0 × 10 −5 to 1.1 × 10 −4 S cm −1 at room temperature and exhibited good electrochemical stability. A solid-state Li/LiFePO4 cell assembled with hybrid solid electrolyte composed of 70 wt.% LAGP, 21 wt.% PEO-LiClO4 and 9 wt.% SN delivered a high discharge capacity and exhibited good capacity retention at ambient temperature. Good cycling performance of the cell resulted from the high ionic conductivity of the solid electrolyte and its good interfacial contacts with electrodes.